Kepercayaan Publik, Kualitas Pelayanan Fiskus Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus Wajib Pajak Orang Pribadi Di Daerah Bantul) - Novi Bergita Paot (Jurnal Sosial Ekonomi Bisnis, 2022)
Purpose: To prove the effect of Public Trust, Quality of Fiscal Service and Tax Sanctions on Individual Taxpayer Compliance (Case Study of Individual Taxpayers in Bantul Region). Methods: The sample of this research is individual taxpayers registered at KPP Pratama Bantul. The sample was selected by purposive sampling method. The total sample is 180 respondents with the sampling technique of cluster random sampling method. Findings: The findings of this study indicate that public trust has a positive effect on taxpayer compliance. The quality of tax services has a positive effect on individual taxpayer compliance and tax sanctions have a positive effect on individual taxpayer compliance. Novelty: The novelty in this study is that public trust is a determinant of increasing taxpayer compliance in carrying out the obligation to pay and report taxes. This research was conducted to strengthen the results of previous research and existing theories.